2004
DOI: 10.1111/j.1399-543x.2004.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glucose tolerance in Egyptian beta-thalassemic patients: possible association with genotyping

Abstract: Abnormal glucose tolerance is common in multiply transfused beta-thalassemia major patients, which could be attributed to progressive and early loss of beta-cell mass, along with persistent insulin resistance. Chronic hepatitis C may play a role in the development of abnormal glucose tolerance. An association between diabetes and genotyping IVS II nt 745 was found. Patients with this particular genotype are advised to check their blood glucose every 6 months to detect early occurrence of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
6
33
2
Order By: Relevance
“…The mean age observed in the present study was close to that of Chern et al [4] (14.8 ± 6.9 years) and comparable with the other study from Tehran (15.20 ± 3.1 years) and a study by Khalifa et al [5] (15.9 ± 3.1 years). In a study by Najafipour F et al [6] in Iran reported mean age was 15.62 ± 4.44 with youngest patient being 10 years and oldest being 27 years.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age observed in the present study was close to that of Chern et al [4] (14.8 ± 6.9 years) and comparable with the other study from Tehran (15.20 ± 3.1 years) and a study by Khalifa et al [5] (15.9 ± 3.1 years). In a study by Najafipour F et al [6] in Iran reported mean age was 15.62 ± 4.44 with youngest patient being 10 years and oldest being 27 years.…”
Section: Resultssupporting
confidence: 92%
“…In a study by Najafipour F et al [6] in Iran reported mean age was 15.62 ± 4.44 with youngest patient being 10 years and oldest being 27 years. In another study by Khalifa et al [5] showed age range of patients to be 10-30 years as compared to the present study where the age range is 10-23 years. In the present study majority of the patients (80%) were males with male to female ratio of 4:1.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Similar findings were observed in another study [34]. Higher age was reported in few studies [25][26][27][28][29]. The probable reasons of patients presented at higher age in these studies were that they enrolled the patients with advance age or their patients have received fewer blood transfusions as compare to our study so as the complications of iron overload may have manifested in advance age group.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are comparable to those explained [25] in Iran. However, higher frequencies were reported in India [26], in Egypt [27], in Cyprus [28], in Oman [29] and in Tehran [30]. Poor iron chelation could be the most likely cause.…”
Section: Discussionmentioning
confidence: 99%